2013
DOI: 10.1371/journal.pone.0061301
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific Effect of Juvenile Diet on Adult Disease Resistance in a Field Cricket

Abstract: Food limitation is expected to reduce an individual’s body condition (body mass scaled to body size) and cause a trade-off between growth and other fitness-related traits, such as immunity. We tested the condition-dependence of growth and disease resistance in male and female Gryllus texensis field crickets by manipulating diet quality via nutrient content for their entire life and then subjecting individuals to a host resistance test using the live bacterium Serratia marcescens. As predicted, crickets on a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(63 citation statements)
references
References 63 publications
4
58
1
Order By: Relevance
“…Results of several other studies on insects and other animals are concordant with our finding (e.g. McVean et al ., ; Klemola et al ., ; Oarada et al ., ; Kelly & Tawes, ). On the other hand, the hypothesis that stress due to poor nutritional conditions promotes disease is also well established, as numerous studies have found poor developmental nutrition to have negative effects on an individual's ability to resist parasites and pathogens (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Results of several other studies on insects and other animals are concordant with our finding (e.g. McVean et al ., ; Klemola et al ., ; Oarada et al ., ; Kelly & Tawes, ). On the other hand, the hypothesis that stress due to poor nutritional conditions promotes disease is also well established, as numerous studies have found poor developmental nutrition to have negative effects on an individual's ability to resist parasites and pathogens (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…We used data presented in Kelly and Tawes () to compare the performance of the scaled mass index with that of two other commonly used approaches (residual index and ANCOVA). Kelly and Tawes () examined the interaction between nutritional quality (poor vs. good diet) during development and sex on various fitness‐related traits, including body condition, at adulthood. This data set comprised information on the body size (pronotum length, mm) and body mass (g) at eclosion for n = 82 females and n = 92 males (see Kelly and Tawes for details).…”
Section: Methodsmentioning
confidence: 99%
“…) or using residual body mass (Wagner and Hoback ; Andrade and Mason ; Whattam and Bertram ; Harrison et al. ), with only a few adopting the newly developed scaled mass index (e.g., Kelly and Tawes ; Stahlschmidt et al. ; Kelly et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A phenotype characterized by effective immune defence, often accompanied by relatively long development time and/or small body size, is frequently observed in insects in challenging nutritional conditions (Sheldon & Verhulst, ; McVean et al ., ; Klemola et al ., ; Kelly & Tawes, ; Krams et al ., ). Accordingly, in the present study, poor larval diet had a positive effect on adult encapsulation response in female moths, whereas having negative effects on development speed and body mass in both sexes.…”
Section: Discussionmentioning
confidence: 99%